2017
DOI: 10.1515/hukin-2017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Elastic Hamstring Assistance Device During Downhill Running

Abstract: The purpose of this study was to determine the appropriateness of using an elastic hamstring assistance device to reduce perceived levels of soreness, increase isometric strength, increase passive range of motion, and decrease biomarkers of muscle damage after eccentric exercise, specifically, downhill running This study was conducted in a university exercise physiology laboratory placing sixteen apparently healthy males ( = 21.6 ± 2.5 years) into two groups using a pre-test/post-test design. Pre-intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At that time, their active resistance to ground impact is likely to have been reduced as indicated by their impaired braking phase in the DJ test at POST. Although information is scarce in the literature regarding the hamstring involvement and fatigue in downhill running, Aldret et al (2017) reported DOMS and a decreased MVC of hamstrings 12 h after a downhill treadmill run. This study included a control group of runners (equipped with an elastic hamstring assistance device) who presented less indirect markers of hamstring damage.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, their active resistance to ground impact is likely to have been reduced as indicated by their impaired braking phase in the DJ test at POST. Although information is scarce in the literature regarding the hamstring involvement and fatigue in downhill running, Aldret et al (2017) reported DOMS and a decreased MVC of hamstrings 12 h after a downhill treadmill run. This study included a control group of runners (equipped with an elastic hamstring assistance device) who presented less indirect markers of hamstring damage.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results showed that XPED2 can reduce the total joint torque by 27.3%. Note that there are also some powered designs inspired by the extracorporeal tendon [69] [70].…”
Section: B Synthetic Passive Exoskeletonsmentioning
confidence: 99%
“…Regarding the hamstring muscle group, Aldret et al 30 . reported that indirect markers of hamstring damage 12 h after a downhill treadmill run were lower in a group of runners equipped of an elastic hamstring assistance device compared to a group of runners without the device.…”
Section: Discussionmentioning
confidence: 99%
“…The reported protective effect of estrogens is therefore questioned. 15 Regarding the hamstring muscle group, Aldret et al 30 reported that indirect markers of hamstring damage 12 h after a downhill treadmill run were lower in a group of runners equipped of an elastic hamstring assistance device compared to a group of runners without the device. In the present study, inflammation lasted in this muscle group until D3-4.…”
Section: Structural Recoverymentioning
confidence: 99%